2020
DOI: 10.3389/fneur.2020.580507
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of COVID-19 Pandemic on People With Multiple Sclerosis

Abstract: The coronavirus disease 2019 has radically changed the world in a few weeks. Italy has been one of the first and most affected countries with more than 30,000 deaths up to now. Public health measures as quarantine or national lockdown are necessary to limit the spread of infectious diseases, but it is unsurprising that depriving people of their liberty has negative psychological effects. This is especially the case for people with chronic diseases, including neurological conditions like multiple sclerosis (MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
95
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(105 citation statements)
references
References 59 publications
9
95
0
1
Order By: Relevance
“…Overall, there are recent studies that have also revealed a negative mental health impact in PwMS that have not tested positive during the current pandemic. These studies found a higher prevalence of depression and anxiety than usual ( Motolese et al, 2020 ; Talaat et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Overall, there are recent studies that have also revealed a negative mental health impact in PwMS that have not tested positive during the current pandemic. These studies found a higher prevalence of depression and anxiety than usual ( Motolese et al, 2020 ; Talaat et al, 2020 ).…”
Section: Discussionmentioning
confidence: 96%
“…In Multiple Sclerosis (MS), there are studies suggesting a negative impact of this pandemic on the mental health of patients with MS (PwMS). For example, a study done in Italy explored how the lockdown period impacted on the mental health of patients in comparison with healthy controls ( Motolese et al, 2020 ). The authors reported that, MS patients, compared with the general population, presented a higher burden of depressive symptoms, a worse sleep quality and perceived an increase in fatigue level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ongoing COVID-19 pandemic has created a lot of anxiety among MS patients, their families and physicians who care for patients with MS. In comparison to the general population, MS patients have had higher rates of depression, worse sleep quality, and fatigue during the pandemic [ 91 ]. Additionally, many MS patients are concerned about their DMT-regimens during the pandemic and some have even stopped it [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…The psychological impact of COVID-19 in terms of stress, negative emotional reactions (e.g., anxiety, depression), and traumatic responses has been extensively studied in the general population [ 39 ] and to a lower extent also in vulnerable populations, such as chronically ill patients, including patients with MS [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, young adults are particularly vulnerable and at greater risk of developing adverse psychological symptoms during the pandemic, as demonstrated in a study by Forte and colleagues [ 40 ] that focused on people under the age of 50.…”
Section: Discussionmentioning
confidence: 99%